Pengaruh Kualitas Produk, Kualitas Pelayanan, dan Harga, terhadap Kepuasan Pelanggan pada Usaha Jajanan Pasar Sari Roso di Kabupaten Blitar - Hekmah Wardina; Muhammad Alhada Fuadilah Habib (VISA: Journal of Vision and Ideas, 2023)
The Sari Roso snack market is one of the large MSME culinary delights in Selopuro District. In the midst of a lot of competition with similar products, the Sari Roso snack market has succeeded in achieving high sales. This is influenced by product quality, service quality, and price. This research aims to determine the influence of product quality, service quality and price on customer satisfaction at the Sari Roso snack market. The population in this research are consumers who have purchased products at the Sari Roso snack market in Ploso Village. This research uses an associative method with a quantitative approach. The sampling technique in this research used an accidental sampling technique with 100 respondents. Data analysis used multiple regression with the help of the IBM SPSS statistics 26 application. The results of this research show that together product quality, service quality and price have a significant effect on customer satisfaction. Then, partially product quality has a positive and significant influence on customer satisfaction. Service quality has a positive and significant influence on customer satisfaction. Also, price has a positive and significant influence on customer satisfaction.